BUDAYA INDONESIA: REFLEKSI ANTARTEKS UNTUK KESEJAHTERAAN BERSAMA - PM Laksono (LITERASI: Indonesian Journal of Humanities, 2014)
The motto of unity in diversity since has been introduced since the time of Majapahit as a spirit to appreciate cultural diversity. Concepts and theories employed here as perspective and the presented cases show that as the effects of acculturation crisis, the Indonesian culture becomes more appropriate when it is accessed with a productive intertextual reflection. The intertextual reflection on Bimasoetji showed the productivity of creative process to produce history. The readers are able to exploit Bimasoetji script or friction that exists to show a prosperity-producing new identity. On the other hand, deceptions as happening to the recitation of the superiority of Obahorok, a head of Dani tribe, just delay welfare. The event fails to correspond the structured world experience, and the ways or emergency tactics that are inherent in the body and mind to move the shared history, remove prejudice to converge in the common welfare. Keywords: Indonesian culture, Bimosoetji, intertextuality, welfare